Diversity of Herpetofauna in and around the Koshi Tappu Wildlife Reserve - Chhetry, Damodar Thapa (BIBECHANA, 2010)
The paper deals with the herpetofauna of Koshi Tappu Wildlife Reserve and its surroundings. A total of 23 species of herpetofauna belonging to 19 genera and 13 families were recorded. Of these 8 species belonging to 6 genera and 3 families were amphibians, and 15 species belonging to 13 genera and 10 families were reptiles. Keywords: herpetofauna; Gavialis gangeticus; Koshi Tappu DOI: 10.3126/bibechana.v6i0.3933 BIBECHANA Vol. 6, March 2010 pp.15-17